Method for preparing large-size formamidine lead iodide perovskite thin film through co-evaporation method
During the preparation of FAPbI3 perovskite film by co-evaporation, the problem of poor crystallinity of perovskite film is solved by converting it into a pure δ-FAPbI3 phase under vacuum conditions and forming a large-size α-FAPbI3 phase by annealing. The photovoltaic performance of perovskite solar cells has been significantly improved.
Patent Information
- Application Number
- CN202411132591.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the process of preparing FAPbI3 perovskite films in the co-evaporation method, the purity of the perovskite phase is difficult to control, resulting in poor crystallinity of the film, affecting the photoelectric conversion efficiency of perovskite solar cells.
A one-step co-evaporation method was used to prepare a mixed phase film containing α-FAPbI3 and δ-FAPbI3, which was then deposited under vacuum and extended the treatment time so that it completely transformed into a pure δ-FAPbI3 phase, and then converted to a large-size α by annealing treatment. -FAPbI3 phase avoids the formation of mesophases and improves the crystallinity of the film.
The prepared FAPbI3 perovskite film has large size and high crystallinity, which significantly improves the photovoltaic performance of perovskite solar cells, including open circuit voltage, short circuit current density and fill factor, and improves the photoelectric conversion efficiency.
Smart Images

Figure CN119136624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite materials, and in particular relates to a method for preparing a large-size formamidine lead iodine perovskite film by a co-evaporation method. Background Art
[0002] Metal halide perovskite solar cells have become a hot topic for researchers due to their excellent optoelectronic properties and low cost. Among them, the "black photoactive" cubic phase formamidinium lead iodide (α-FAPbI3) is often used in the preparation of light-absorbing materials in perovskite solar cells due to its narrow optical band gap (Eg) and good thermal stability. However, FA with a larger ion size + The lattice distortion caused by this will cause α-FAPbI3 to be easily transformed into "yellow non-photoactive" δ-FAPbI3, thereby damaging the photoelectric conversion efficiency of solar cells. Therefore, the preparation of high-quality FAPbI3 (formamidinium lead iodine) perovskite films should avoid the formation of δ-FAPbI3 phase. However, in the process of preparing FAPbI3 film by co-evaporation, if the film after evaporation is directly transformed from an unstable α-FAPbI3 and δ-FAPbI3 mixed phase into a more stable α-FAPbI3 phase, the prepared film has a smaller grain size, and there are more δ-FAPbI3 in the film that has not been completely converted into α-FAPbI3. To improve this problem, Xie Weiguang et al. found that the addition of an appropriate amount of water molecules can effectively reduce the energy barrier between the α-FAPbI3 phase and the δ-FAPbI3 phase, thereby promoting the formation of α-FAPbI3 (Advanced Functional Materials, 2022: 2208392). However, this method will also be accompanied by the formation of an intermediate phase between 6H-FAPbI3 and 4H-FAPbI3, thereby reducing the formation rate of α-FAPbI3, causing the perovskite film to exhibit poor crystallinity, which in turn affects the photoelectric conversion efficiency of perovskite solar cells.
[0003] Therefore, in the preparation process of high-efficiency FAPbI3-based perovskite solar cells, the formation of the intermediate phase of the FAPbI3 perovskite film should be avoided, the crystallinity of the perovskite film should be improved, and the performance of the perovskite solar cell should be improved. Summary of the invention
[0004] The present invention aims to solve the technical problem that in the current process of preparing FAPbI3 perovskite thin films by the co-evaporation method, the purity of the perovskite mineral phase is difficult to control, resulting in poor crystallinity of the film. The present invention provides a method for preparing large-sized formamidinium lead iodide perovskite thin films by the co-evaporation method. The preparation method adopts a one-step co-evaporation method and combines vacuum treatment and annealing treatment processes to prepare a stable high-crystallinity α-FAPbI3 thin film. The α-FAPbI3 thin film of the present invention is applied to solar cells and has excellent photovoltaic performance.
[0005] The inventive concept of the present invention is: first, based on a one-step co-evaporation method, PbI2 and FAI exist in the gas phase at the same time, and are uniformly mixed and reacted to prepare a FAPbI3 perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3. Then, the deposition is carried out for a sufficient time under vacuum conditions. On the one hand, the FAPbI3 perovskite film does not have too many water molecules under vacuum conditions to affect the phase change path of α-FAPbI3, which can effectively avoid the problem of impure phase of the FAPbI3 perovskite film; on the other hand, the vacuum treatment time is appropriately extended to make the perovskite completely transformed from an unstable α-FAPbI3 and δ-FAPbI3 mixed phase into a stable pure δ-FAPbI3 phase, ensuring that there is no δ-FAPbI3 phase residue. Finally, annealing treatment is performed to cause larger crystals to transform from the δ-FAPbI3 phase to the α-FAPbI3 phase, and the prepared FAPbI3 perovskite film has the characteristics of large size and high crystallinity.
[0006] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a formamidinium lead iodine perovskite film, comprising the following steps:
[0007] (1) Co-evaporation of PbI2 and FAI on a substrate to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3;
[0008] (2) vacuum treating the perovskite film containing the mixed phase of α-FAPbI3 and δ-FAPbI3 to form a pure δ-FAPbI3 phase perovskite film;
[0009] (3) Annealing the pure δ-FAPbI3 phase perovskite film to form the pure α-FAPbI3 phase formamidine lead iodide perovskite film.
[0010] Preferably, in step (1), the evaporation temperature of PbI2 is 305-315°C.
[0011] Preferably, in step (1), the evaporation temperature of FAI is 155-165°C.
[0012] Preferably, in step (1), the evaporation rate ratio of PbI2 and FAI is (1-2.2): 1. Studies have found that the evaporation rate ratio of PbI2 and FAI has a great influence on the performance of formamidinium lead iodide perovskite film. As the evaporation rate of PbI2 and FAI decreases, the open circuit voltage of the perovskite solar cell will be significantly reduced, and the non-radiative recombination of carriers in the perovskite solar cell will gradually increase, thereby reducing the photoelectric conversion efficiency.
[0013] Preferably, in step (2), the pressure of the vacuum treatment is less than 1×10 -3 Torr.
[0014] Preferably, in step (2), the vacuum treatment time is 10-14 hours. After vacuum treatment, the "brown" perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 becomes a "yellow" pure δ-FAPbI3 phase perovskite film.
[0015] Preferably, in step (3), the temperature of the annealing treatment is 150-160°C.
[0016] Preferably, in step (3), the annealing treatment time is 18-23 minutes.
[0017] Preferably, in step (3), the ambient humidity of the annealing treatment is lower than 25%. By reducing the ambient humidity, the influence of water molecules on the phase transition path of α-FAPbI3 can be reduced, thereby improving the purity of the α-FAPbI3 phase.
[0018] Preferably, in step (1), the substrate is FTO conductive glass with an electron transport layer coated on the surface.
[0019] Preferably, the electron transport layer is a metal oxide.
[0020] Preferably, the metal oxide film is a SnO2 layer, and the SnO2 layer is deposited on the surface of the FTO conductive glass by chemical deposition.
[0021] The second aspect of the present invention provides a formamidinium lead iodine perovskite film, wherein the formamidinium lead iodine perovskite film is prepared by the above-mentioned preparation method, and the perovskite grain size distribution in the formamidinium lead iodine perovskite film is between 0.4-1 μm. The perovskite crystals in the formamidinium lead iodine perovskite film prepared by the preparation method of the present invention are large in size and have the characteristics of high crystallinity.
[0022] A third aspect of the present invention provides a solar cell, comprising the formamidinium lead iodide perovskite thin film.
[0023] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0024] (1) In the process of preparing the formamidinium lead iodine perovskite film of the present invention, a one-step co-evaporation method is first adopted to make PbI2 and FAI exist in the gas phase at the same time and mix and react evenly to obtain a FAPbI3 perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then, deposition is carried out for a period of time under vacuum conditions to completely transform the perovskite from an unstable mixed phase of α-FAPbI3 and δ-FAPbI3 to a stable pure δ-FAPbI3 phase; finally, annealing treatment is performed to cause larger crystals to transform from the δ-FAPbI3 phase to the α-FAPbI3 phase. The prepared formamidinium lead iodine perovskite film has the characteristics of large size and high crystallinity, and has good repeatability, and is suitable for the preparation of large-size films.
[0025] (2) The present invention adopts a vacuum environment to process the crystal transformation, thereby improving the perovskite grain size problem and transforming it from an unstable mixed phase of α-FAPbI3 and δ-FAPbI3 into a stable pure δ-FAPbI3 phase; at the same time, through annealing treatment, larger crystals are transformed from δ-FAPbI3 to α-FAPbI3, which is beneficial to improving the efficiency of transmitting and collecting carriers and enhancing the energy conversion efficiency of the battery.
[0026] (3) The perovskite film prepared by the present invention has no holes and high phase purity. When applied to solar cells, the open circuit voltage can reach 1116mV and the short circuit current density can reach 23.69mA / cm 2 , the filling factor can reach 0.753, and the forward scan photoelectric conversion efficiency can reach 19.9%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The SEM images and particle size statistics of the FAPbI3 perovskite films prepared in Example 1 and Comparative Example 1;
[0028] Figure 2 XRD diagram of the FAPbI3 perovskite film prepared in Example 1 and Comparative Examples 1-2;
[0029] Figure 3 The current-voltage characteristic curves of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2;
[0030] Figure 4 This is a current-voltage characteristic curve of the perovskite solar cell prepared in Comparative Example 3;
[0031] Figure 5 This is a current-voltage characteristic curve of the perovskite solar cell prepared in Comparative Example 4;
[0032] Figure 6 The performance evolution diagram of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0034] Example 1
[0035] A method for preparing a formamidinium lead iodine perovskite film comprises the following steps:
[0036] (1) 1.096 g of SnO2·2H2O solid, 5 g of urea, 5 mL of concentrated hydrochloric acid, 100 μL of thioglycolic acid and 400 mL of deionized water were placed in a wide-mouthed Shu Niu bottle, shaken and mixed thoroughly to obtain a SnO2 stock solution, which was then stored in a refrigerator and aged for 12 hours before use;
[0037] (2) Place the cleaned FTO conductive glass in a UV cleaning machine for ultraviolet irradiation for 15 minutes; then, take 20 mL of SnO2 stock solution and 100 mL of deionized water; after stirring evenly, place it in an ultrasonic cleaning machine for ultrasonic treatment for 2 minutes to obtain a diluted SnO2 solution; place the UV-cleaned FTO conductive glass face up in a glass box, and add the SnO2 diluted solution; wrap the glass box with plastic wrap, place it in a 90°C oven, and keep it warm for 3 hours; then, clean the surface of the FTO conductive glass with deionized water, and blow dry the glass surface with nitrogen; finally, place the FTO conductive glass on a hot plate at 180°C, keep it warm for 1 hour, and after the FTO conductive glass cools to room temperature, place it in a clean box and store it for later use;
[0038] (3) Weigh appropriate amounts of PbI2 and FAI (PbI2 mass is 1.2 g) and co-evaporate them on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 2:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then place the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 in a vacuum chamber at a pressure of less than 1×10 -3Torr evaporator for 12 hours; in a vacuum environment, the mixed phase of α-FAPbI3 and δ-FAPbI3 is transformed into a stable pure δ-FAPbI3 phase perovskite film;
[0039] (4) The pure δ-FAPbI3 phase perovskite film obtained in step (3) is placed on a heating platform at 155° C. and annealed for 20 min to form a pure α-FAPbI3 phase formamidine lead iodide perovskite film.
[0040] A method for preparing a perovskite solar cell comprises the following steps:
[0041] (1) Weigh 500 mg of Li-TFSI, dissolve it in 1 mL of acetonitrile, shake it thoroughly to mix it evenly, and prepare it as lithium salt for later use; weigh 520 mg of trivalent cobalt-based complex FK209, dissolve it in 1 mL of acetonitrile, shake it thoroughly to mix it, and prepare it as cobalt salt for later use; weigh 73 mg of Spiro-OMeTAD powder and dissolve it in 1 mL of chlorobenzene, add 18 μL of lithium salt, 29 μL of cobalt salt and 30 μL of 4-tert-butylpyridine (TBP) respectively, and shake the solution on a shaker for 30 min;
[0042] (2) Using a pipette, 20 μL of the prepared Spiro-OMeTAD solution was drawn and evenly coated on the surface of the sample obtained in step (1); then, spin-coated at a speed of 3000 rpm / s for 30 seconds to prepare a Spiro-OMeTAD hole transport layer;
[0043] (3) Place the sample in step (2) into the mask plate and use a vacuum coating machine to evacuate the chamber to a vacuum of 1×10 - 3 Torr, and An 80nm gold electrode was evaporated at an evaporation rate to obtain a perovskite solar cell.
[0044] Example 2
[0045] A method for preparing a formamidinium lead iodine perovskite film comprises the following steps:
[0046] (1) 1.096 g of SnO2·2H2O solid, 5 g of urea, 5 mL of concentrated hydrochloric acid, 100 μL of thioglycolic acid and 400 mL of deionized water were placed in a wide-mouthed Shu Niu bottle, shaken and mixed thoroughly to obtain a SnO2 stock solution, which was then stored in a refrigerator and aged for 12 hours before use;
[0047] (2) Place the cleaned FTO conductive glass in a UV cleaning machine for ultraviolet irradiation for 15 minutes; then, take 20 mL of SnO2 stock solution and 100 mL of deionized water; after stirring evenly, place it in an ultrasonic cleaning machine for ultrasonic treatment for 2 minutes to obtain a diluted SnO2 solution; place the UV-cleaned FTO conductive glass face up in a glass box, and add the SnO2 diluted solution; wrap the glass box with plastic wrap, place it in a 90°C oven, and keep it warm for 3 hours; then, clean the surface of the FTO conductive glass with deionized water, and blow dry the glass surface with nitrogen; finally, place the FTO conductive glass on a hot plate at 180°C, keep it warm for 1 hour, and after the FTO conductive glass cools to room temperature, place it in a clean box and store it for later use;
[0048] (3) Weigh appropriate amounts of PbI2 and FAI (PbI2 mass is 1.2 g) and co-evaporate them on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 1:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then place the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 in a vacuum chamber at a pressure of less than 1×10 -3 Torr evaporator for 10 hours; in a vacuum environment, the α-FAPbI3 and δ-FAPbI3 mixed phase is transformed into a stable pure δ-FAPbI3 phase perovskite film;
[0049] (4) The pure δ-FAPbI3 phase perovskite film obtained in step (3) is placed on a heating platform at 150° C. and annealed for 18 minutes to form a pure α-FAPbI3 phase formamidine lead iodide perovskite film.
[0050] The preparation method of the perovskite solar cell of Example 2 is the same as that of Example 1.
[0051] Example 3
[0052] A method for preparing a formamidinium lead iodine perovskite film comprises the following steps:
[0053] (1) 1.096 g of SnO2·2H2O solid, 5 g of urea, 5 mL of concentrated hydrochloric acid, 100 μL of thioglycolic acid and 400 mL of deionized water were placed in a wide-mouthed Shu Niu bottle, shaken and mixed thoroughly to obtain a SnO2 stock solution, which was then stored in a refrigerator and aged for 12 hours before use;
[0054] (2) Place the cleaned FTO conductive glass in a UV cleaning machine for ultraviolet irradiation for 15 minutes; then, take 20 mL of SnO2 stock solution and 100 mL of deionized water; after stirring evenly, place it in an ultrasonic cleaning machine for ultrasonic treatment for 2 minutes to obtain a diluted SnO2 solution; place the UV-cleaned FTO conductive glass face up in a glass box, and add the SnO2 diluted solution; wrap the glass box with plastic wrap, place it in a 90°C oven, and keep it warm for 3 hours; then, clean the surface of the FTO conductive glass with deionized water, and blow dry the glass surface with nitrogen; finally, place the FTO conductive glass on a hot plate at 180°C, keep it warm for 1 hour, and after the FTO conductive glass cools to room temperature, place it in a clean box and store it for later use;
[0055] (3) Weigh appropriate amounts of PbI2 and FAI (PbI2 mass is 1.2 g) and co-evaporate them on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 2.2:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then place the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 in a vacuum chamber at a pressure of less than 1×10 -3 Torr evaporator for 14 hours; in a vacuum environment, the mixed phase of α-FAPbI3 and δ-FAPbI3 is transformed into a stable pure δ-FAPbI3 phase perovskite film;
[0056] (4) The pure δ-FAPbI3 phase perovskite film obtained in step (3) is placed on a heating platform at 160° C. and annealed for 23 min to form a pure α-FAPbI3 phase formamidine lead iodide perovskite film.
[0057] The preparation method of the perovskite solar cell of Example 3 is the same as that of Example 1.
[0058] Comparative Example 1
[0059] The only difference between Comparative Example 1 and Example 1 is that, in the preparation process of formamidinium lead iodide perovskite film, step (3) does not contain a vacuum treatment step, specifically: weigh appropriate amounts of PbI2 and FAI (PbI2 mass is 1.2 g), and co-evaporate them on the SnO2-coated substrate prepared in step (2) at a evaporation rate ratio of 2:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3.
[0060] Comparative Example 2
[0061] The only difference between Comparative Example 2 and Example 1 is that in the preparation process of formamidinium lead iodide perovskite film, the vacuum treatment in step (3) is replaced by high humidity treatment, specifically: weigh appropriate amounts of PbI2 and FAI (PbI2 mass is 1.2 g), and co-evaporate them on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 2:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then transfer the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 to an acrylic glove box with a humidity of 80%, and wait for 5-10 minutes to allow the color of the perovskite film to change to "yellow".
[0062] Comparative Example 3
[0063] The difference between Comparative Example 3 and Example 1 is that, in the preparation process of the formamidinium lead iodine perovskite film, the evaporation rate ratio in step (3) is smaller, specifically: weigh appropriate amounts of PbI2 and FAI (the mass of PbI2 is 1.2 g), and co-evaporate them on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 0.75:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then place the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 in a vacuum chamber at a pressure of less than 1×10 -3 Torr evaporator for 12 hours; in a vacuum environment, the mixed phase of α-FAPbI3 and δ-FAPbI3 is transformed into a stable pure δ-FAPbI3 phase perovskite film.
[0064] Comparative Example 4
[0065] The difference between Comparative Example 4 and Example 1 is that, in the preparation process of the formamidinium lead iodine perovskite film, the vacuum treatment time in step (3) is shorter, specifically: weigh appropriate amounts of PbI2 and FAI (the mass of PbI2 is 1.2 g), co-evaporate on the SnO2-coated substrate prepared in step (2) at an evaporation rate ratio of 2:1 to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; then place the perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3 in a vacuum chamber at a pressure of less than 1×10 -3 Torr evaporator for 6 hours; in a vacuum environment, the mixed phase of α-FAPbI3 and δ-FAPbI3 is transformed into a stable δ-FAPbI3 phase perovskite film.
[0066] Performance Testing
[0067] 1. Microstructure
[0068] Figure 1 The SEM images and particle size distribution diagrams of the FAPbI3 perovskite films prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen from the comparison that the vacuum treated perovskite ( Figure 1 The crystal size of c) is smaller than that of the perovskite without vacuum treatment ( Figure 1 a) is significantly improved, and the density of the film is also significantly improved. The average grain size of Example 1 is 615nm ( Figure 1 d), compared with the average grain size of 333nm ( Figure 1 b), has also been significantly improved.
[0069] 2.XRD test
[0070] Figure 2 The XRD diagrams of the FAPbI3 perovskite films prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 2 The horizontal axis 2Theta represents the 2θ diffraction angle, the vertical axis Intensity represents the intensity of the diffraction peak, and Ref, 80% RH and vacuum represent the XRD spectra of the FAPbI3 perovskite films prepared in Comparative Example 1, Comparative Example 2 and Example 1, respectively. Figure 2 It can be seen that the half-peak width of Comparative Example 1 under normal pressure is the largest, indicating that the crystallinity of the film is the worst. Comparative Example 2 under high humidity has the lowest half-peak width, but there are a small amount of 4H-FAPbI3, 6H-FAPbI3 and PbI2 in the film, indicating that the purity of the perovskite phase is not high. Example 1 has a lower half-peak width than Comparative Example 1, indicating that vacuum conditions are conducive to improving the crystallinity of the film, which further confirms that Figure 1 In addition, no diffraction peaks other than α-FAPbI3 were observed in Example 1, indicating that no other secondary phases exist in the perovskite.
[0071] 3. Photovoltaic performance
[0072] Figure 3 The current-voltage characteristic curves of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 3 a. Figure 3 b and Figure 3 c respectively represent the current-voltage characteristic curves of the perovskite solar cells prepared in Comparative Example 1, Comparative Example 2 and Example 1, and the specific results are shown in Table 1. Wherein: Voc represents the open circuit voltage, Jsc represents the short circuit current density, Fill Factor represents the filling factor, Efficienty photoelectric conversion efficiency, Reverse Scan (RS) represents forward scanning, and Forward Scan (FS) represents reverse scanning.
[0073] Table 1:
[0074]
[0075] Depend on Figure 3 As shown in Table 1, the photovoltaic performance of the perovskite solar cell prepared in Example 1 is better than that of Comparative Examples 1-2, and the photoelectric conversion efficiency can reach 19.9% in the positive scan, while the photoelectric conversion efficiency decreases under non-vacuum conditions or high humidity conditions. At the same time, the photovoltaic performance of the perovskite solar cell prepared in Examples 2-3 is equivalent to that of Example 1.
[0076] Figure 4-5 They are the current-voltage characteristic curves (positive scan) of the perovskite solar cells prepared in Comparative Examples 3-4, and the specific results are shown in Table 2.
[0077] Table 2:
[0078]
[0079] Depend on Figure 4-5 As shown in Table 2, with the decrease of PbI2 and FAI evaporation rate, the open circuit voltage (V OC ) is significantly reduced, indicating that the non-radiative recombination of carriers in the perovskite solar cell is gradually intensified. Therefore, the photoelectric conversion efficiency of the perovskite solar cell continues to decrease with the decrease of the PbI2 and FAI evaporation rates. When the vacuum treatment time is shortened, the "brown" perovskite film containing α-FAPbI3 and δ-FAPbI3 mixed phases fails to be completely transformed into a "yellow" pure δ-FAPbI3 phase perovskite film, which limits the photoelectric conversion efficiency of the perovskite solar cell. This shows that the performance of the formamidinium lead iodine perovskite film of the present invention is closely related to the preparation parameters.
[0080] 4. Battery performance evolution
[0081] Figure 6 The performance evolution diagram of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2. Figure 6 The figure shows that the solar cell prepared in Example 1 (vacuum group) has the highest open circuit voltage (VOC), indicating that the perovskite solar cell prepared in the present invention has the lowest carrier non-radiative recombination. In addition, the solar cell has the lowest hysteresis index (H-index), and the reduction of this value indicates that the ion migration inside the perovskite film of the vacuum group is alleviated and the defect state density is reduced. This shows that the solar cell of the vacuum group has the highest photoelectric conversion efficiency (PCE).
[0082] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing a formamidinium lead iodine perovskite film, characterized in that: The following steps are involved: (1) Co-evaporation of PbI2 and FAI on a substrate to form a perovskite film containing a mixed phase of α-FAPbI3 and δ-FAPbI3; (2) vacuum treating the perovskite film containing the mixed phase of α-FAPbI3 and δ-FAPbI3 to form a pure δ-FAPbI3 phase perovskite film; (3) Annealing the pure δ-FAPbI3 phase perovskite film to form the pure α-FAPbI3 phase formamidine lead iodide perovskite film.
2. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 1, characterized in that: In step (1), the evaporation temperature of PbI2 is 305-315°C; and / or the evaporation temperature of FAI is 155-165°C.
3. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 2, characterized in that: The evaporation rate ratio of PbI2 and FAI is (1-2.2):
1.
4. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 1, characterized in that: In step (2), the vacuum treatment pressure is less than 1×10 -3 Torr; and / or, the vacuum treatment time is 10-14 hours.
5. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 1, characterized in that: In step (3), the annealing temperature is 150-160° C.; and / or the annealing time is 18-23 min.
6. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 1, characterized in that: In step (3), the ambient humidity of the annealing treatment is lower than 25%.
7. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 1, characterized in that: In step (1), the substrate is FTO conductive glass with an electron transport layer coated on the surface.
8. The method for preparing the formamidinium lead iodine perovskite thin film according to claim 7, characterized in that: The electron transport layer is a metal oxide film.
9. A formamidinium lead iodine perovskite film, characterized in that: The formamidinium lead iodine perovskite film is prepared by the preparation method according to any one of claims 1 to 8, and the perovskite grain size distribution in the formamidinium lead iodine perovskite film is between 0.4 and 1 μm.
10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the formamidinium lead iodide perovskite thin film according to claim 9.
Citation Information
Patent Citations
Perovskite thick film X-ray detector and preparation method thereof
CN112768609A
